South Africa : The Cyclical Behavior of the Markups and its Implications for Monetary Policy - Klein, Nir. (Washington, D.C. : International Monetary Fund, 2011)
The study looks at the cyclical behavior of the markups and assesses its impact on inflation dynamics. The analysis finds that the aggregate level of the private sector's markup is relatively high, thus pointing to the lack of strong competition in South Africa's product markets. Additionally, the results suggest that the markups tend to move in a countercyclical manner, with a short-term positive impact on inflation. This implies that the countercyclical pattern of the markups is one factor among others that contribute to the relatively weak output gap-inflation co-movement. In the context of South Africa's inflation targeting framework, the counter-cyclical markups may also generate an asymmetric response of monetary policy to the fluctuations in economic activity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet